Importance of intraoperative indocyanine green imaging in the management of non-occlusive mesenteric ischemia: a case report - Ryohei Miyashita; Masato Kitazawa; Shigeo Tokumaru; Satoshi Nakamura; Makoto Koyama; Yuta Yamamoto; Nao Hondo; Satoru Miyazaki; Yuji Soejima (Surgical Case Reports, 2023)
Abstract Background Non-obstructive intestinal ischemia (NOMI) is caused by intestinal vascular spasm and has a poor prognosis if not diagnosed and treated early. Indocyanine green (ICG) fluorescence imaging has been reported to be useful for the intraoperative assessment of the extent of intestinal resection required for NOMI. Few reports have described massive intestinal bleeding after conservative management of NOMI. We report a case of NOMI with massive postoperative bleeding from the site of an ICG contrast defect found before the initial surgery. Case presentation A 47-year-old woman with hemodialysis-dependent chronic kidney disease presented complaining of severe abdominal pain. A computed tomography scan showed portal gas and dilation of the small intestine, leading to a diagnosis of NOMI and subsequent emergency surgery. At the time of initial surgery, the contrast effect of ICG was slightly reduced, showing a granular distribution in the ascending colon to cecum (fine grain pattern) and significantly reduced in parts of the terminal ileum except around blood vessels (perivascular pattern). However, there was no obvious gross necrosis of the serosal surface, and the intestinal tract was not resected. The acute postoperative course was uneventful; however, the patient went into shock on the 24th postoperative day due to massive, small intestinal bleeding, and emergency surgery was performed. The bleeding originated from the section of the ileum that had complete loss of ICG contrast effect before the initial surgery. A right hemicolectomy with the terminal ileum resection was performed, and an ileo-transverse anastomosis was performed. The second post-operative course was uneventful. Conclusions We report a case of delayed hemorrhage of the ileum shown to have poor blood flow on ICG imaging at the initial surgery. Intraoperative ICG fluorescence imaging is useful in assessing the degree of intestinal ischemia for NOMI. When patients with NOMI are followed up without surgery, complications such as bleeding should be noted.